Choroidal and Retinal Thickness of Highly Myopic Eyes with Early Stage of Myopic Chorioretinopathy: Tessellation. (11th February 2018) - Zhou, Yanping; Song, Minlu; Zhou, Minwen; Liu, Yiming; Wang, Fenghua; Sun, Xiaodong
Abstract : Purpose . To investigate the choroidal thickness (CT) and retinal thickness (RT) in highly myopic tessellated eyes. Methods . In this study, 115 highly myopic eyes were recruited and divided as tessellated fundus (n = 93 ) and normal fundus (n = 22 ). RT and CT were quantified using optical coherence tomography with enhanced depth imaging (EDI-OCT). Correlation between subfoveal CT (SFCT) and tessellation was analyzed using logistic regression models. Results . Tessellated fundus eyes had thinner CT than did normal fundus eyes, while RT was not statistically different across groups. The tessellated eyes had a thinner choroid than did the control eyes at all measured macular locations (allP < 0.05 ). After adjustment for AL, age, and gender, the SFCT was significantly associated with tessellation. The odds ratio (OR) and 95% confidence interval (CI) was 0.975 (0.960–0.990, P = 0.001, binary logistics regression) and 0.991 (0.984–0.999, P = 0.022, Cox regression). The area under the curve (AUC) of SFCT was the greatest for detecting tessellation (AUC = 0.824, P < 0.001 ). For sensitivity and specificity analyses, SFCT had the highest diagnostic value (sensitivity = 81.8%, specificity = 74.2%). Conclusions . Highly myopic eyes with tessellation have thinner CT than do normal highly myopic eyes. CT may serve as an early pathologic predictor of high myopia.